Marker-assisted hop (Humulus lupulus L.) breeding: Biochemical markers for resistance to downy mildew (Pseudoperonospora humuli Miyabe et Takah) and hop damson aphid (Phorodon humuli Schrank) - Kralj, Dragica; Kač, Milica; Dolinar, Marta; Žolnir, Milan; Kralj, Samo (BrewingScience, 1998)
The resistance to hop damson aphid (Phorodon humuli Schrank) is related to a combination of three markers in the hop essential oil: alpha-pinene, beta-pinene and the undefined peak 92. The accession is resistant if the oil contains the compound 92 and the index ratios of alpha-pinene to peak 92 and beta-pinene to peak 92 are sufficiently low (critical value is 4). If one of the ratios is above these critical values, the accession is susceptible. The resistance to downy mildew (Pseudoperonospora humuli Miyabe et Takah) is related to 9 independent markers present in the essential oil if at least one of them is present in amount above the critical index. The critical index is the threshold above which the marker becomes responsible for susceptibility of the accession to downy mildew. In non European accessions 4 markers (peak 33, iso-amyl-iso-butyrate, trans-ocimene, geraniol) and in European accessions 5 markers (methyl caprinate, alpha-humulene, peak 68, methyl-deca-4-enoate and peak 51) have been observed. The accession is resistant to downy mildew if alpha-humulene is present below the critical index and the indexes for the rest of the markers are below the detection limit or are relatively low.